Kampung 3G (Glintung Go Green): Ide Lokal Sebagai Solusi Global? - Ervina Fredayani (Sospol : Jurnal Sosial Politik, 2018)
This paper aims to examine the Village 3G (Glintung Go Green) as a solution in achieving the goals contained in the program SDG (Sustainable Development Goals) made by the United Nations (United Nations). The author discusses environmental issues that form the basis of the creation of very complex issues such as health, hygiene, economics, and society. This research was conducted by the writer using a qualitative descriptive method with interview technique, documentation study with RW 23 Chair Glintung Bambang Irianto, and literature study, and the concept of community empowerment as a way of looking at the phenomena we observed. The author wants to know how the solution offered by Glintung Village in addressing environmental issues in the context of SDGs. In addition, the authors want to know the response of domestic and international communities to the idea of Kampung 3G which is used as a solution to realize the SDG program.